Upaya Penanggulangan Tindak Pidana Penyelundupan Pemalsuan Dokumen Kepabeanan Di Indonesia - Putu Sekarwangi Saraswati (Universitas Mahendradatta, 2019)
The occurrence of these customs smuggling crimes cannot be changed in the sectorof income tax and import duty / excise for the state, but will be able to influence and bringnegative impacts. Where criminal acts can be carried out by bodies that will integrate goodsabroad or translate goods from abroad, for example by providing customs documents thatare not in accordance with goods exported or imported. Acts of smuggling in falsification ofcustoms documents in addition to economic factors, also by factors in Indonesia, quality ofdomestic industrial products, including barriers to entry of certain types of goods, looseningof supervision, others, the perpetrators themselves do not know that they have committedfraud customs documents. Whereas prevention efforts can be done preventively andrefresively.